2018
DOI: 10.1002/stem.2901
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Cheating Death for a Better Transplant

Abstract: Hematopoietic stem cell transplantation is routinely performed for the treatment of various malignant and non-malignant hematological diseases. Successful transplantation depends on the number and fitness of donor stem and progenitor cells, whose quality is substantially influenced by the sampling procedure, sample handling, and cryopreservation. BCL-2 proteins are central to the survival and maintenance of stem and progenitor cells under both, physiological and stress conditions. Transplantation-associated ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…We found earlier that both transplantation and xenotransplantation-associated apoptosis are mediated primarily by the BH3-only proteins BIM and BMF 24 . Even their transient inhibition during the period of transplantation and early engraftment resulted in better transplantation outcomes 51,52 . We, therefore, postulated that additional inhibition of BIM would at least partially improve human engraftment during xenotransplantation but, unexpectedly, did not observe any beneficial effects of this manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…We found earlier that both transplantation and xenotransplantation-associated apoptosis are mediated primarily by the BH3-only proteins BIM and BMF 24 . Even their transient inhibition during the period of transplantation and early engraftment resulted in better transplantation outcomes 51,52 . We, therefore, postulated that additional inhibition of BIM would at least partially improve human engraftment during xenotransplantation but, unexpectedly, did not observe any beneficial effects of this manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, we suggest that p53 GOF is a non-cellautonomous phenomenon, which would make this gene very peculiar if compared with other oncogenes/oncosuppressors, such as KRas 59,60 , Rb 61,62 or Bcl-2 [63][64][65][66][67] . The p53 mutant can dictate instructions to the microenvironment, which in turn are influenced by additional extrinsic factors that direct signals on the cancer cells that are differentially integrated based on the p53 mutational status (Fig.…”
Section: Conclusion: P53 Mutants: One Gene Many Proteins In Many Conmentioning
confidence: 99%
“…We have already showed that inhibition of the intrinsic apoptosis pathway in donor cells, even when limited to a few days around transplantation, significantly improves outcome of HSCT, especially when only low donor cell numbers are available. 18,22,23…”
Section: Discussionmentioning
confidence: 99%